2016
DOI: 10.14797/mdcj-12-2-86
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Imaging in Athletes

Abstract: Athletic heart syndrome refers to the physiological and morphological changes that occur in a human heart after repetitive strenuous physical exercise. Examples of exercise-induced changes in the heart include increases in heart cavity dimensions, augmentation of cardiac output, and increases in heart muscle mass. These cardiac adaptations vary based on the type of exercise performed and are often referred to as sport-specific cardiac remodeling. The hemodynamic effects of endurance and strength training exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
(32 reference statements)
1
16
2
2
Order By: Relevance
“…Implementation of limited echocardiography would allow sports medicine providers to monitor individual athletes' responses to exercise. Sports medicine clinicians could use limited echocardiography to track cardiac morphologic and function changes in their athletes and adjust training loads accordingly . Tracking training load adjustments and their subsequent effects on cardiac morphologic characteristics and function could produce more effective exercise prescriptions while also serving to prevent maladaptive responses to exercise training in elite athletes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of limited echocardiography would allow sports medicine providers to monitor individual athletes' responses to exercise. Sports medicine clinicians could use limited echocardiography to track cardiac morphologic and function changes in their athletes and adjust training loads accordingly . Tracking training load adjustments and their subsequent effects on cardiac morphologic characteristics and function could produce more effective exercise prescriptions while also serving to prevent maladaptive responses to exercise training in elite athletes .…”
Section: Discussionmentioning
confidence: 99%
“…This factor has the potential to dramatically improve training load monitoring and personalized exercise training. The use of limited echocardiography performed by frontline providers to monitor training loads could serve to prevent overtraining syndrome and improve performance …”
Section: Discussionmentioning
confidence: 99%
“…Vytrvalostní sportovci mohou mít klidovou ejekční frakci levé komory při dolní hranici normy. 8 Při zátěži se jejich ejekční frakce zvyšuje. 9 Kromě morfologických změn myokardu se u trénovaných jedinců manifestuje také vagotonie, která se může projevit klidovou sinusovou nebo junkční bradykardií.…”
Section: Atletické Srdceunclassified
“…12,13 Mimo výše zmíněné morfologické varianty EKG je pro trénované jedince také typický sklon ke klidové bradykardii, jež bývá asymptomatická. 8 Povětšinou jde o sinusovou nebo junkční bradykardii, někdy můžeme dokumentovat atrioventrikulární (AV) blokádu II. stupně Wenckebachova typu.…”
Section: Klinické Symptomyunclassified
“…Echocardiography is simple, yet effective in characterizing left ventricular (LV) parameters such as LV end-diastolic diameter (LVEDD) and relative wall thickness in athletes [5][6][7]. Prior studies have observed that these LV remodeling parameters, along with sphericity index, ventricular mass, and wall thickness, are important features in differentiating athletic remodeling [8,9].…”
Section: Introductionmentioning
confidence: 99%